A review on the degradability of polymeric composites based on natural fibres - Azwa, Z.N.; Yousif, B.F.; Manalo, A.C.; Karunasena, W. (Materials in engineering, 2013)
► Natural fibres are prone to moisture attack. ► The amount of fibre in a composite shall be limited to its optimum fibre/matrix ratio to limit its moisture susceptibility. ► Fibre treatments are essential to enhance strength and moisture durability of composite. ► Low lignin content in a natural fibre leads to better thermal performance. The applications of natural fibre/polymer composites in civil engineering are mostly concentrated on non-load bearing indoor components due to its vulnerability to environmental attack. This paper evaluates the characteristics of several natural fibre composites exposed to moisture, thermal, fire, and ultraviolet degradation through an extensive literature review. The effects of chemical additives such as fibre treatments, fire retardants and Ultraviolet (UV) stabilizers are also addressed. Based on the evaluation conducted, optimum fibre content provides strength in a polymer composite but it also becomes an entry point for moisture attack. Several fibre treatments are also being used to improve fibre/matrix interface, thereby increasing moisture durability. However, the treated fibres were found to behave poorly when exposed to weather. The addition of UV stabilizers and fire retardants are suggested to enhance outdoor and fire performance of natural fibre/polymer composite but compromises its strength. Therefore, from the collected data and various experimental results, it was concluded that an optimum blend ratio of chemical additives must be employed to achieve a balance between strength and durability requirements for natural fibre composites.